Sistem Cerdas Distribusi Logistik Bencana: Studi Kasus untuk Penanganan Bencana di Indonesia - Muhammad Yahya; Jumadi Mabe Parenreng; Suhartono Suhartono (Seminar Nasional LP2M UNM, 2019)
Indonesian country is included in areas prone to natural disasters such as earthquakes, tsunamis, volcanic eruptions, landslides, floods, droughts, fires and other natural disasters. The problem of natural disasters faced by Indonesia is not only when natural disasters occur, but also post-disaster handling, especially in distribution of logistic disaster. Common problems include the unequal distribution of aid in the event of a disaster and after a disaster, accumulation of aid in warehouses, slow distribution, and weak coordination between related agencies. The amount of community concern is illustrated by the abundance of aid, if not accompanied by the professionalism of the work of government and related apparatus, the assistance will be less meaningful for people in need. This application facilitates a disaster logistics system that is able to provide accurate information, both of to the government and related authorities as well as to the wider community, whose responsibilities can be overseen by the public. The method of decision making using a decision tree algorithm. The end result will make it easier for search and rescue workers in the field, related to the actions that must be taken, as well as being a media for accountability for the distribution of accurate logistical disasters to the community, government and related authorities. In addition, the importance of this research lies in the level of needs of rescue teams who are in aid posts and residents in refugee camps, where from the aid posts each team works clearly with targets according to the needs of residents who need help and on time because the system has index areas that are indeed a priority. While from the side of the disaster victims community will get assistance according to their needs and on time.